Early Cessation of Breastfeeding and Determinants: Time to Event Analysis. (30th April 2020) - Babaee, Ebrahim; Eshrati, Babak; Asadi-Aliabadi, Mehran; Purabdollah, Majid; Nojomi, Marzieh
Abstract : Background . The onset of breastfeeding has a high success rate in most countries, but the time for termination of breastfeeding varies between countries. Objective . This survey was aimed to determine the effective factors on the early termination of breastfeeding. Methods . This study was conducted in 2018, in Iran. About 410 mothers were enrolled in the study. All considered factors were evaluated as factors influencing the continuity of breastfeeding. Survival analysis was used to analyze data. Results . The mean age of the mothers was equal to 29.48 ± 5.8 years. The frequency of termination of breastfeeding before the first 2 years was equal to 34%. The mean of breastfeeding duration was equal to 21.49 ± 5.3 months. The percentage of infants who had been breastfed for 24 months was equal to 65.8%. An infant's birth weight (2500–4000 gr) (hazard ratio: 0.54), neonatal birth order (hazard ratio: 0.69), neonatal pathologic jaundice (hazard ratio: 1.52), starting time of using complementary food (hazard ratio: 2.45), using pacifier (hazard ratio: 2.82), and the status of using artificial milk (hazard ratio: 3.29) were significantly associated with cessation of breastfeeding before 24 months of age. The probability of termination of breastfeeding at 6, 12, 18, and 24 months of age was reported by 6%, 8%, 15%, and 34%, respectively. Conclusions . There were notifiable variations in breastfeeding rates both in national and international levels. Nevertheless, in this study, the mean of breastfeeding duration was longer compared to a number of countries and previous national studies.